Management Training of Sumatra Elephant (Elephas maximus sumatranus) and Daily Behavior in Flying Squad WWF Tesso Nilo National Park, Riau - Arum Ratnasari; Abdul Haris Mustari; Burhanuddi Masyud (Department of Forest Resources Conservation and Ecotourism - IPB University, 2017)
Flying squad is an established strategy in the effort to resolve the conflict elephants in Tesso Nilo National Park. Flying squad utilizes trainedelephants to chase away wild elephants that come out the national park area. The study aims to identify management training and daily behavior ofSumatran elephant. The study was conducted in the Flying Squad WWF's Tesso Nilo National Park, Riau in March-April 2016 using focal animalsampling and interview. The elephant training curriculum consist of basic training, advanced training and exercise development by combined verbalcommands, visual, and physical. The measured success of training will be seen if the elephants could perform mahout’s commands without any error.Percentage of ingestive behavior showed the highest value at noon, while percentage of shelter seeking and other behavior showed the highest valueat night. It caused the elephants do more displacement to get the food at noon.Keywords: daily behavior, flying squad, focal animal sampling, sumatran elephant, training management